Transforming social perspectives with cognitive maps. Issue 10 (7th March 2022) - Arzy, Shahar; Kaplan, Raphael
Abstract: Growing evidence suggests that cognitive maps represent relations between social knowledge similar to how spatial locations are represented in an environment. Notably, the extant human medial temporal lobe literature assumes associations between social stimuli follow a linear associative mapping from an egocentric viewpoint to a cognitive map. Yet, this form of associative social memory does not account for a core phenomenon of social interactions in which social knowledge learned via comparisons to the self, other individuals or social networks are assimilated within a single frame of reference. We argue that hippocampal–entorhinal coordinate transformations, known to integrate egocentric and allocentric spatial cues, inform social perspective switching between the self and others. We present evidence that the hippocampal formation helps inform social interactions by relating self vs other social attribute comparisons to society in general, which can afford rapid and flexible assimilation of knowledge about the relationship between the self and social networks of varying proximities. We conclude by discussing the ramifications of cognitive maps in aiding this social perspective transformation process in states of health and disease.